Impact of pulmonary embolism response teams on acute pulmonary embolism: a systematic review and meta-analysis. (13th July 2022) - Fleitas Sosa, Derlis; Lehr, Andrew L.; Zhao, Huaqing; Roth, Stephanie; Lakhther, Vlad; Bashir, Riyaz; Cohen, Gary; Panaro, Joseph; Maldonado, Thomas S.; Horowitz, James; Amoroso, Nancy E.; Criner, Gerard J.; et al.
Background: The impact of pulmonary embolism response teams (PERTs) on treatment choice and outcomes of patients with acute pulmonary embolism (PE) is still uncertain. Objective: To determine the effect of PERTs in the management and outcomes of patients with PE. Methods: PubMed, Embase, Web of Science, CINAHL, WorldWideScience and MedRxiv were searched for original articles reporting PERT patient outcomes from 2009. Data were analysed using a random effects model. Results: 16 studies comprising 3827 PERT patients and 3967 controls met inclusion criteria. The PERT group had more patients with intermediate and high-risk PE (66.2%) compared to the control group (48.5%). Meta-analysis demonstrated an increased risk of catheter-directed interventions, systemic thrombolysis and surgical embolectomy (odds ratio (OR) 2.10, 95% confidence interval (CI) 1.74–2.53; p<0.01), similar bleeding complications (OR 1.10, 95% CI 0.88–1.37) and decreased utilisation of inferior vena cava (IVC) filters (OR 0.71, 95% CI 0.58–0.88; p<0.01) in the PERT group. Furthermore, there was a nonsignificant trend towards decreased mortality (OR 0.87, 95% CI 0.71–1.07; p=0.19) with PERTs. Conclusions: The PERT group showed an increased use of advanced therapies and a decreased utilisation of IVC filters. This was not associated with increased bleeding. Despite comprising more severe PE patients, there was a trend towards lower mortality in the PERT group. Pulmonary embolism response teams increase use of advanced therapies for pulmonary embolism without increasing bleeding complications https://bit.ly/39NJZuw